Draft Seventh Five Year Plan 1985-90 and Annual Plan 1985-86 Volume-I Government of Madhya Pradesh - Planning Commission (Planning Commission, 1985)
Madhya Pradesh is the largest State in the Union in terms of area. It occupies about 443 sq. kms., roughly about one-seventh area of the count covers 76.6 thousand villages and 327 towns. The Population of the State is 521.3 lakh(1981 census) which approximately one-thirteenth of the country's population large segment of this population is composed of Scheduled Tribes and Scheduled Castes. They combinedly 37 per cent of the total population and the tribe instituting 23 per cent are the dominant partners.
Government of Madhya Pradesh, Planning, Economics and Statistics Department